Numerical Aperture for Photon Detection within Shifted Position-Diffuse Reflectance Imaging - Späth, Moritz; Hohmann, Martin; Rohde, Maximilian; Klämpfl, Florian (OSA Technical Digest (Optical Society of America, 2021), 2021)
Shifted position-diffuse reflectance imaging is used to non-invasively assess microcirculation. In this study, it is investigated whether a cut-off angle in the detection of the reflected photons is obligatory for the success of the technique.<br